Determinant Banking Credit Risk Management - Josua Panatap Soehaditama; Nera Marinda Machdar; Adler Haymans Manurung (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article reviews and looks for the relationship between two variables, namely banking and credit risk management from the results of existing research. The research method used is qualitative by looking at the findings or research results from existing literature derived from reputable journals or other sources found to support this study. In this article explains that banking credit risk management, determinants play an important role in identifying, measuring, and managing credit risk. Factors such as debtor characteristics, quality of collateral, economic and industrial conditions, bank policies and procedures, and legal and regulatory factors affect the level of credit risk. A deep understanding of these factors helps banks in taking better decisions and developing effective strategies in managing credit risk.